2002
DOI: 10.1086/338890
|View full text |Cite
|
Sign up to set email alerts
|

Burst Oscillation Periods from 4U 1636−53: A Constraint on the Binary Doppler Modulation

Abstract: The burst oscillations seen during Type I X-ray bursts from low mass X-ray binaries (LMXB) typically evolve in period towards an asymptotic limit that likely reflects the spin of the underlying neutron star. If the underlying period is stable enough, measurement of it at different orbital phases may allow a detection of the Doppler modulation caused by the motion of the neutron star with respect to the center of mass of the binary system. Testing this hypothesis requires enough X-ray bursts and an accurate opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 28 publications
6
73
1
Order By: Relevance
“…X-ray studies of 4U 1636−53 have shown a variety of variability on different time scales ranging form mHz to kHz. The NS nature of the compact object has been confirmed through the detection of thermonuclear X-ray bursts (Hoffman et al 1977;Galloway et al 2006;Zhang et al 2011), which show asymptotic millisecond burst oscillations, indicating a spin frequency of ∼581 Hz (Zhang et al 1997;Giles et al 2002;Strohmayer & Markwardt 2002). In addition to variability studies, the X-ray energy spectra, which show broad, asymmetric Fe emission lines, have been investigated (Pandel et al 2008;Cackett et al 2010;Ng et al 2010;Sanna et al 2013).…”
Section: U 1636−53mentioning
confidence: 93%
See 1 more Smart Citation
“…X-ray studies of 4U 1636−53 have shown a variety of variability on different time scales ranging form mHz to kHz. The NS nature of the compact object has been confirmed through the detection of thermonuclear X-ray bursts (Hoffman et al 1977;Galloway et al 2006;Zhang et al 2011), which show asymptotic millisecond burst oscillations, indicating a spin frequency of ∼581 Hz (Zhang et al 1997;Giles et al 2002;Strohmayer & Markwardt 2002). In addition to variability studies, the X-ray energy spectra, which show broad, asymmetric Fe emission lines, have been investigated (Pandel et al 2008;Cackett et al 2010;Ng et al 2010;Sanna et al 2013).…”
Section: U 1636−53mentioning
confidence: 93%
“…Since then the source has been observed over a wide range of wavelengths. Optical photometry revealed an orbital period of ∼3.8 h (van Paradijs et al 1990), and a companion star with a mass of ∼0.4 M , assuming an NS mass of 1.4 M (Giles et al 2002). X-ray studies of 4U 1636−53 have shown a variety of variability on different time scales ranging form mHz to kHz.…”
Section: U 1636−53mentioning
confidence: 99%
“…X-ray studies of 4U 1636-53 have shown a variety of rapid time variability, including i) thermonuclear X-ray bursts (e.g. Hoffman et al 1977;Galloway et al 2006;Zhang et al 2011), confirming the presence of a NS as the compact object, ii) millisecond oscillations during the X-ray bursts, indicating a spin frequency of ∼581 Hz (Zhang et al 1997;Giles et al 2002;Strohmayer & Markwardt 2002), and iii) kHz quasi-periodic oscillations (kHz QPOs, e.g. Wijnands et al 1997;Belloni et al 2007;Altamirano et al 2008;Sanna et al 2012).…”
Section: U 1636-53mentioning
confidence: 99%
“…2.18 # 10 the oscillations have been searched at the known frequency (which does not evolve by more than ≈6 Hz; Giles et al 2002), multiplying by the number (p3) of trials, we get a significance of , which implies a ∼4 j detection. We also fit…”
Section: ϫ5mentioning
confidence: 99%